Penanganan Pasien dengan Gangguan Pola Tidur Menggunakan Terapi Bekam Basah: Laporan Kasus - mukhlish hidayat; Ahmadi Ahmadi; Atika Jatimi; Fahrur Rosi Ali (Indonesian Health Science Journal, 2023)
Introduction: Hypertension is the cause of various serious diseases and complications. One of the signs and symptoms of hypertension is difficulty sleeping. Therefore it is necessary to improve the quality of sleep so that the blood pressure of someone who suffers from hypertension does not increase and can be controlled properly. One of the alternative treatments that are widely used by people today is alternative medicine with cupping therap. Objectives: The purpose of this study is to describe nursing care by applying cupping therapy procedures to improve sleep quality in hypertensive patients. Methods: This research uses a case study descriptive method by analyzing in depth a research object whose unit of analysis is individual from assessment, diagnosis, intervention, implementation and evaluation. Respondents amounted to two people with a medical diagnosis of hypertension. Results: The results showed that on the fourth day P1 and P2 said they had no difficulty sleeping, no dizziness, no pacing, not supported by objective data the patient did not appear restless, with an interpretation of the assessment the problem was resolved. Conclusions: After being given nursing care with the application of wet cupping therapy to 2 patients, it can be concluded that wet cupping therapy can improve sleep quality in hypertensive patients.